Design of a Microcontroller-Based Photo-Controlled Circuit for Adjusting the Speed of DC Motors (Al-Mansour Journal, 2022)
There are many approaches and methods for changing the speed of DC motors. One of these approaches is through the intensity of light. In this paper, a microcontroller-based control circuit for adjusting the speed of a DC motor by means of interrupting the incident light is proposed and implemented. The adopted technique in this circuit uses two light dependent resistors as photo-sensors to detect the illumination of light by producing a prescribed digital sequence to activate one of the input ports of an 8051 microcontroller. An assembly program stored in the on-chip program memory of the microcontroller generates the proper PWM signal at an output port based on the received sequence. This signal is supplied to the driving circuit of the motor in order to run it with the relevant speed. The circuit has been implemented and tested successfully in the laboratory
Keywords: 8051 Microcontroller; Motor Speed Control; PWM; Photo- sensors